Frontline combination of ponatinib and hyper‐CVAD in Philadelphia chromosome‐positive acute lymphoblastic leukemia: 80‐months follow‐up results. Issue 3 (4th January 2023) - Kantarjian, Hagop; Short, Nicholas J.; Jain, Nitin; Sasaki, Koji; Huang, Xuelin; Haddad, Fadi G.; Khouri, Issa; DiNardo, Courtney D.; Pemmaraju, Naveen; Wierda, William; Garcia‐Manero, Guillermo; Kebriaei, Partow; et al.
Abstract: The combination of ponatinib, a third‐generation BCR::ABL1 tyrosine kinase inhibitor, with hyper‐CVAD chemotherapy resulted in high rates of complete molecular remissions and survival, without the need for stem cell transplantation (SCT) in most patients with Philadelphia chromosome(Ph)‐positive acute lymphocytic leukemia (ALL). Confirming these results in a large cohort of patients with longer follow‐up would establish this regimen as a new standard of care. Adults with newly diagnosed Ph‐positive ALL were treated with the hyper‐CVAD regimen. Ponatinib was added as 45 mg daily × 14 during induction, then 45 mg daily continuously (first 37 patients) or 30 mg daily continuously, with dose reduction to 15 mg daily upon achievement of a complete molecular response (CMR; absence of a detectable BCR::ABL1 transcript by quantitative reverse transcription polymerase‐chain reaction at a sensitivity of 0.01%). Maintenance therapy consisted of daily ponatinib and vincristine‐prednisone monthly for 2 years, followed by daily ponatinib indefinitely. Twelve intrathecal injections of cytarabine alternating with methotrexate were given as central nervous system prophylaxis. The trial is registered on clinicaltrials.gov with the identifier NCT01424982. Eighty‐six patients were treated. Their median age was 46 years (range, 21–80). All 68 patients with active disease at the initiation of therapy achieved complete response (CR) The cumulative CMR rate was 86%. Twenty‐ patients (23%) underwent allogeneic SCT. With a median follow‐up of 80 months (range, 16–129 months), the estimated 6‐year event‐free survival rate was 65% and the overall survival rate was 75%. There was no difference in outcome by performance of allogeneic SCT in first CR. Common grade 3–5 adverse events included infection ( n  = 80, 93%), increased liver transaminases ( n  = 26, 31%) and total bilirubin ( n  = 13, 15%), hypertension ( n  = 15, 17%), pancreatitis ( n  = 13, 15%), hemorrhage ( n  = 12, 13%), and skin rash ( n  = 9, 10%). Two ponatinib‐related deaths from myocardial infarction (3%; at months 2.6 and 4.3, respectively; both in CR) in the first 37 patients treated led to the ponatinib dose‐modifications mentioned earlier, with no further ponatinib‐related deaths observed. The long‐term results of ponatinib and hyper‐CVAD continue to demonstrate excellent outcome results and acceptable safety data, indicating that this strategy is another standard of care approach in frontline Ph‐positive ALL.